1998
DOI: 10.1038/sj.onc.1202126
|View full text |Cite
|
Sign up to set email alerts
|

FGF-3 and FGF-4 elicit distinct oncogenic properties in mouse mammary myoepithelial cells

Abstract: Fibroblast Growth Factors 3 (FGF-3) and 4 (FGF-4) were compared for the e ects they each exert on EF43 mouse cells. This non-transformed mammary cell line appears to be myoepithelial mainly because it expresses a-smooth muscle actin. The EF43 cells were infected with similar vectors that carry either the short fgf-3 sequence (the product of which goes into the secretory pathway), fgf-4 or the selection gene only as control. In syngeneic animals, EF43.fgf-3 cells were tumorigenic only when orthotopically implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…[37][38][39] Furthermore, some genes such as FGF-3 and rsc (rabbit squamous cell carcinoma) have potent oncogenic activities in nude mice, but do not induce anchorage-independent growth in the semi-solid media. 36,40,41) HDGF seems to belong to this group. Although NIH3T3-HDGF stable transfectants could not form large colonies in semi-solid media, but they did form more small colonies than the mock or parent cells in the soft agar assay.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Furthermore, some genes such as FGF-3 and rsc (rabbit squamous cell carcinoma) have potent oncogenic activities in nude mice, but do not induce anchorage-independent growth in the semi-solid media. 36,40,41) HDGF seems to belong to this group. Although NIH3T3-HDGF stable transfectants could not form large colonies in semi-solid media, but they did form more small colonies than the mock or parent cells in the soft agar assay.…”
Section: Discussionmentioning
confidence: 99%
“…We found that FGF-3 exerts a specific effect, which differs from the mode of action of FGF-4, a known oncogenic product [22]. The present work was thus undertaken to investigate what was the effect of an fgf-3 expression in human mammary cells.…”
Section: Introductionmentioning
confidence: 98%
“…AAVP-transduced HSVtk also may act as a cell suicide-inducing gene in the presence of ganciclovir (GCV), which is converted by the thymidine kinase enzyme to a cytotoxic compound (36). To investigate the efficacy of the GRP78-targeting AAVP in breast cancer treatment, we used the syngeneic EF43.fgf4 mammary tumor model (25,37). Five days after tumor cell implantation, mice received an i.v.…”
Section: Grp78 Is Strongly Expressed In Human Ibcmentioning
confidence: 99%